2015
DOI: 10.3889/oamjms.2015.096
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematosus and Secondary Antiphospholipid Syndrome after Thymectomy for Myasthenia Gravis - A Case Report

Abstract: INTRODUCTION:Systemic lupus erythematosus (SLE) and myasthenia gravis (MG) are autoimmune diseases that show some similarities: a higher incidence in young women, relapsing-remitting course and positive anti-nuclear antibodies (ANA). However, they are two different clinical syndromes, which can coexist or precede each other. Thymectomy is a therapeutic option for patients with severe MG or thymoma. There are many cases of SLE after thymectomy described in the literature, so the question arises whether thymecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Similar to large studies on polyautoimmunity,24 female predominance is also seen in our review with only one male patient having APAS and MG 14. SLE was also found in three of the patients 14 25. A systematic review found that patients with MG who are seropositive are 3.68 times more likely to develop other autoimmune disease compared with those who are seronegative 22.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to large studies on polyautoimmunity,24 female predominance is also seen in our review with only one male patient having APAS and MG 14. SLE was also found in three of the patients 14 25. A systematic review found that patients with MG who are seropositive are 3.68 times more likely to develop other autoimmune disease compared with those who are seronegative 22.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is supported in our review with 6 out of the 7 of the cases with available laboratory data,9 11–14 testing positive for the anti-acetylcholinesterase (anti-AChR) antibody. Four9 11 12 25 out of the five reviewed cases who underwent thymectomy developed APAS after the procedure. A study involving a small cohort of patients with patients with MG suggests that thymectomy may be related to the development of other autoimmune diseases26 because of the loss of central tolerance and overproduction of antibodies 23.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that thymectomy should not be attempted in SLE patients unless a thymoma is present ( 2 ). This contention is substantially supported by at least five reports in the English literature ( 11 - 15 ), which have even reported new-onset SLE after thymectomy.…”
Section: Discussionmentioning
confidence: 78%
“…SLE and MG have similar features and precede one another or can coexist in a patient, which is a rare association [2]. They both have a higher incidence in the female population and both exhibit positive anti-nuclear antibodies [5]. The association between SLE and MG has been reported, which is seen in patients undergoing thymectomy for MG, for example, a case report of a 48-year-old female mentions the occurrence of SLE and secondary antiphospholipid syndrome (APS) 28 years post thymectomy for MG, with thymectomy being the precipitating factor [5].…”
Section: Introductionmentioning
confidence: 99%
“…They both have a higher incidence in the female population and both exhibit positive anti-nuclear antibodies [5]. The association between SLE and MG has been reported, which is seen in patients undergoing thymectomy for MG, for example, a case report of a 48-year-old female mentions the occurrence of SLE and secondary antiphospholipid syndrome (APS) 28 years post thymectomy for MG, with thymectomy being the precipitating factor [5]. Thymic abnormalities are commonly seen with MG patients; thus, thymectomy is considered as the first line of management in case of generalized or severe myasthenia as the thymus is known for autoantibody production [3,6].…”
Section: Introductionmentioning
confidence: 99%